Effect of Different Fermentation Condition on Estimated Glycemic Index, In Vitro Starch Digestibility, and Textural and Sensory Properties of Sourdough Bread - Demirkesen-Bicak, Hilal; Arici, Muhammet; Yaman, Mustafa; Karasu, Salih; Sagdic, Osman (MDPI, 2021)
This study aimed to evaluate the influence of sourdough fermentation on the estimated glycemic index (eGI), in vitro starch digestibility, and textural and sensory properties of eight experimentally prepared sourdough breads. Wheat and whole wheat flour bread samples were produced under different fermentation conditions (25 degrees C and 30 degrees C) and fermentation methods (type-1 and type-2). In type-1 fermentation, sourdough was obtained via spontaneous fermentation. Indigenous strains (Lactobacillus brevis ELB99, Lactiplantibacillus plantarum ELB75, and Saccharomyces cerevisiae TGM55) were used for type-2 fermentation. Fermentation type and temperature significantly affected eGI, the hydrolysis index (HI), the starch fraction, and the textural properties of the samples (p < 0.05). The resistant starch (RS) content increased after fermentation, while rapidly digestible starch (RDS), HI, and eGI decreased. RS values were significantly higher in type-2 than in type-1 at the same temperature for both flour types (p < 0.05). At 25 degrees C, RS values were higher in both fermentation types. In the white flour samples, eGI values were in the range of 60.8-78.94 and 62.10-78.94 for type-1 and type-2, respectively. The effect of fermentation type on eGI was insignificant (p < 0.05). In the whole flour samples, fermentation type and temperature significantly affected eGI (p < 0.05). The greatest eGI decreases were in whole wheat sourdough bread at 30 degrees C using type-2 (29.74%). The 30 degrees C and type-2 samples showed lower hardness and higher specific volume. This study suggests that fermentation type and temperature could affect the eGI and the textural and sensory properties of sourdough bread, and these factors should be considered during bread production. The findings also support the consumption of wheat and whole wheat breads produced by type-2 fermentation due to higher RS and slowly digestible starch (SDS) and lower RDS and eGI values.
Keywords: sourdough; starch fractions; fermentation; glycemic index; bread; texture; NUTRITIONAL PROPERTIES; ORGANIC-ACIDS; WHEAT BREAD; FIBER; HYDROLYSIS; STABILITY; IMPACT; RYE; Food Science & Technology